Peningkatan Hasil Belajar Soal Cerita Kelipatan Persekutuan Terkecil Dan Faktor Persekutuan Terbesar dengan Strategi Polya di Kelas IV SD Dian Andalas Kota Padang - Lita, Rina; Masniladevi, Masniladevi; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research aims at improving students’ abilities to solve Mathematical Word Problems about LCM and GCD by using the Polya Strategy at Class IV of SD Dian Andalas, Padang. This Class action research applied both qualitative an quantitative approaches. The subject were the teacher as an observer, the researcher as a practitionaire, and the students of the class. The research result shows some improvements. In term of lesson plans, the score increased from 76.79% in cycle I to 92.86 in cycle II. In term of teacher’s aspect, the score enhanced from 75% in cycle I to 90.63% in cycle II. Meanwhile, in term of the student’s aspect, the score increased from 65.63% in cycle I to 90.63% in cycle II. Finally, the student’s learning outcomes enhanced from 76.18 in cycle I to 85.23 in cycle II.